Anaerobic oxidation of methane by manganese oxides in marine sediments: a review - Xue, Yuan; Lu, Hailong; Li, Yan; Yang, Hailin; Tang, Yukai; Lu, Yinghan (Frontiers in Marine Science, 2025)
Anaerobic oxidation of methane (AOM) is a key methane sink in marine sediments, driven by electron acceptors such as sulfate, nitrate, and metal oxides. Manganese (Mn) oxides, owing to their high oxidizing capacity and rapid turnover, are also recognized as critical oxidants in AOM. However, Mn-AOM has not been well reviewed although several relevant studies have been published. In this paper, current results about Mn-AOM are summarized by synthesizing its geochemical characteristics, pathways for manganese activity, and microbial communities involved under certain marine environments. Two dominant pathways have been proposed for microbial involvement in Mn-AOM in marine sediments: direct AOM coupled to Mn oxide reduction, and indirect AOM via Mn oxide-mediated sulfate reduction. Mn-AOM activity is observed in methane-rich cold seeps or continental margins with substantial Mn oxides input. Future research efforts are still needed to prioritize quantifying the role of Mn-AOM in global carbon and marine manganese cycles.